Ex vivo analysis of root canal cleaning using Endo-PTC associated to NaOCl and different irrigant solutions - Andrea Kanako Yamazaki; Cacio Moura-Netto; Ricardo Julio Cabrales Salgado; Brigida Monica Kleine; Igor Prokopowitsch (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this study was to assess qualitatively, by means of SEM images, the cleaning of the dentin walls of root canals after chemical-surgical preparation using Endo-PTC cream with 0.5% and 1% sodium hypochlorite and different final irrigating solutions. Seventy-two single-rooted human teeth were divided into eight groups and prepared using Endo-PTC cream with sodium hypochlorite (NaOCl) at different concentrations, and irrigated with NaOCl at different concentrations. Final irrigation was performed with either EDTA-T or EDTA-C. The best results were obtained with Group 1, followed by Groups 5, 2, 7, 8, 3, 6 and 4. We can conclude that the use of 0.5% NaOCl during instrumentation and final flush of the root canals was more efficient in cleaning than was 1% sodium hypochlorite. EDTA-T was more efficient in removing smear layer than EDTA-C, and the cervical third presented better cleaning of the root canal walls than did the middle third, which showed cleaner dentin walls than the apical third.